Surveying death roll behavior across Crocodylia. Issue 4 (4th July 2019) - Drumheller, Stephanie K.; Darlington, James; Vliet, Kent A.
Abstract : The "death roll" is an iconic crocodylian behaviour, and yet it is documented in only a small number of species, all of which exhibit a generalist feeding ecology and skull ecomorphology. This has led to the interpretation that only generalist crocodylians can death roll, a pattern which has been used to inform studies of functional morphology and behaviour in the fossil record, especially regarding slender-snouted crocodylians and other taxa sharing this semi-aquatic ambush predator body plan. In order to test this hypothesis, we surveyed death roll behaviour across animals representing all extant crocodylian species. Animals were prompted to death roll using two methods of stimulation: a feeding cue and an escape cue. The feeding cue involved presenting each animal with a bait item, to which resistance would be applied during a biting event. The second cue involved capturing each animal with a rope or catch pole, a standard technique for capturing crocodylians, but one that also often prompts an attempt to escape. All species tested, except Paleosuchus palpebrosus, exhibited the behaviour in response to at least one of the stimuli. This included the following slender-snouted species: Gavialis gangeticus, Tomistoma schlegelii, Mecistops cataphractus, Mecistops leptorhynchus, Crocodylus johnstoni, and Crocodylus intermedius . The patterns of death roll behavior observed in this survey suggest that this behaviour is not novel to any one crocodylian clade, morphotype, or dietary niche. Also, the prevalence of death rolling behaviour across Crocodylia in response to perceived threats indicates that it is not solely, or maybe even primarily, a feeding behaviour, but is also utilised during inter- and intra-specific conflict as a means to escape or injure an opponent. The results of this case study highlight the importance of using multiple modern analogues when attempting to correlate form and function across diverse clades, both living and extinct.